A novel maturation index based on neonatal diffusion tensor imaging reflects typical perinatal white matter development in humans. Issue 56 (14th December 2016) - Rasmussen, Jerod M.; Kruggel, Frithjof; Gilmore, John H.; Styner, Martin; Entringer, Sonja; Consing, Kirsten N.Z.; Potkin, Steven G.; Wadhwa, Pathik D.; Buss, Claudia
Abstract: Human birth presents an abrupt transition from intrauterine to extrauterine life. Here we introduce a novel Maturation Index (MI) that considers the relative importance of gestational age at birth and postnatal age at scan in a General Linear Model. The MI is then applied to Diffusion Tensor Imaging (DTI) in newborns for characterizing typical white matter development in neonates. DTI was performed cross‐sectionally in 47 neonates (gestational age at birth = 39.1 ± 1.6 weeks [GA], postnatal age at scan = 25.5 ± 12.2 days [SA]). Radial diffusivity (RD), axial diffusivity (AD) and fractional anisotropy (FA) along 27 white matter fiber tracts were considered. The MI was used to characterize inflection in maturation at the time of birth using GLM estimated rates of change before and after birth. It is proposed that the sign (positive versus negative) of MI reflects the period of greatest maturation rate. Two general patterns emerged from the MI analysis. First, RD and AD (but not FA) had positive MI on average across the whole brain (average MIAD = 0.31 ± 0.42, average MIRD = 0.22 ± 0.34). Second, significant regions of negative MI in RD and FA (but not AD) were observed in the inferior corticospinal regions, areas known to myelinate early. Observations using the proposed method are consistent with proposed models of the white matter maturation process in which pre‐myelination is described by changes in AD and RD due to oligodendrocyte proliferation while true myelination is characterized by changes in RD and FA due to myelin formation.